An Exploration of the Link between Development, Economic Growth,and Natural Risk - Hallegatte, Stephane (2012)
This paper investigates the link between development, economic growth, and the economic losses from natural disasters in a general analytical framework, with an illustration on hurricane flood risks in New Orleans. It concludes that, where capital accumulates through increased density of capital at risk in a given area, (i) the probability of disaster occurrence decreases with income; (ii) capital at risk and thus economic losses in case of disaster – increases faster than economic growth; (iii) increasing risk-taking reinforces economic growth. Economic growth and improved protection transfer risks from frequent low-intensity events to rarer high-impact events. In this context, average annual losses from disasters grow with income, and they grow faster than income at low levels of development and slower than income at high levels of development. These findings are robust to a broad range of modeling choices and parameter values, to the inclusion of risk aversion, and to variations in the decision-making framework (including the introduction of prospect theory's decision weights, biases in risk perception and myopic expectations). They show that risk-taking is both a driver and a consequence of economic development, that risk taking should not be indiscriminately suppressed, and that the world is very likely to experience fewer but more costly disasters in the future.
MAG ID: 1808689159

Managing the Risks of Extreme Events and Disasters to Advance Climate Change Adaptation, A Special Report of Working Groups I and II of the Intergovernmental Panel on Climate Change - Intergovernmental Panel on Climate Change (IPCC) (Cambridge University Press, 2012)
Keywords: Ouvrage_Collectif_Numéro1

Determinants of Risk: Exposure and Vulnerability - Cardona, Omar-Dario; Van Aalst, Maarten K.; Birkmann, Jörn; Fordham, Maureen; McGregor, Glenn; Perez, Rosa; Pulwarty, Roger S.; Schipper, E. Lisa F.; Sinh, Bach Tan; Décamps, Henri; Keim, Mark; Davis, Ian; et al. (Managing the Risks of Extreme Events and Disasters to Advance Climate Change Adaptation, 2012)
Keywords: Ouvrage_Collectif_Numéro1